2013
DOI: 10.1097/eja.0b013e32835df608
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deep vs. awake extubation on respiratory complications in high-risk children undergoing adenotonsillectomy

Abstract: Australian New Zealand Clinical Trials Registry: ACTRN12609000387224.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 16 publications
(19 reference statements)
2
62
1
3
Order By: Relevance
“…This would result in a calculated absolute difference of 25%. The basis for the power analysis assumptions was not provided in this report . The investigators found no difference in hypoxemia or laryngospasm but reported an increased incidence of persistent coughing following an awake extubation and airway obstruction relieved by simple airway maneuvers following a deep extubation .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This would result in a calculated absolute difference of 25%. The basis for the power analysis assumptions was not provided in this report . The investigators found no difference in hypoxemia or laryngospasm but reported an increased incidence of persistent coughing following an awake extubation and airway obstruction relieved by simple airway maneuvers following a deep extubation .…”
Section: Discussionmentioning
confidence: 98%
“…The basis for the power analysis assumptions was not provided in this report . The investigators found no difference in hypoxemia or laryngospasm but reported an increased incidence of persistent coughing following an awake extubation and airway obstruction relieved by simple airway maneuvers following a deep extubation . Although the extubation technique was not standardized, deep extubation was defined as an endtidal sevoflurane concentration >1 minimum alveolar concentration.…”
Section: Discussionmentioning
confidence: 99%
“…They increase intracranial or intraocular pressure (eg, following open eye surgery) but also venous pressure in the head and neck and could favor bleeding (eg, following adenotonsillectomy and cleft palate repair). It should also be kept in mind that they are potential causes of laryngotracheal damage and bronchospasm and that they increase intrathoracic pressure with a risk of acute right to left shunting in case of intracardiac defect . Last but not least, coughing results in apnea at the end of a forced expiration and thus reduces the pulmonary O 2 reserve before extubation.…”
Section: Awake or Deep Extubation?mentioning
confidence: 99%
“…In skilled hands, the timing of extubation (awake vs. deep) in healthy children with normal airways does not appear to affect outcomes . However, the mantra in the low‐resource setting is to extubate children awake because of the variability in pediatric anesthesia training, support, and resources.…”
Section: Challenges In Postoperative Carementioning
confidence: 99%